Marinobacter salarius sp. nov. and Marinobacter similis sp. nov., isolated from sea water. - Hooi Jun Ng (Public Library of Science (PLoS), 2014)
Two non-pigmented, motile, Gram-negative marine bacteria designated R9SW1T and A3d10T were isolated from sea water samples collected from Chazhma Bay, Gulf of Peter the Great, Sea of Japan, Pacific Ocean, Russia and St. Kilda Beach, Port Phillip Bay, the Tasman Sea, Pacific Ocean, respectively. Both organisms were found to grow between 4 °C and 40 °C, between pH 6 to 9, and are moderately halophilic, tolerating up to 20% (w/v) NaCl. Both strains were found to be able to degrade Tween 40 and 80, but only strain R9SW1T was found to be able to degrade starch. The major fatty acids were characteristic for the genus Marinobacter including C16:0, C16:1ω7c, C18:1ω9c and C18:1ω7c. The G+C content of the DNA for strains R9SW1T and A3d10T were determined to be 57.1 mol% and 57.6 mol%, respectively. The two new strains share 97.6% of their 16S rRNA gene sequences, with 82.3% similarity in the average nucleotide identity (ANI), 19.8% similarity in the in silico genome-to-genome distance (GGD), 68.1% similarity in the average amino acid identity (AAI) of all conserved protein-coding genes, and 31 of the Karlin's genomic signature dissimilarity. A phylogenetic analysis showed that R9SW1T clusters with M. algicola DG893T sharing 99.40%, and A3d10T clusters with M. sediminum R65T sharing 99.53% of 16S rRNA gene sequence similarities. The results of the genomic and polyphasic taxonomic study, including genomic, genetic, phenotypic, chemotaxonomic and phylogenetic analyses based on the 16S rRNA, gyrB and rpoD gene sequence similarities, the analysis of the protein profiles generated using MALDI-TOF mass spectrometry, and DNA-DNA relatedness data, indicated that strains R9SW1T and A3d10(T) represent two novel species of the genus Marinobacter. The names Marinobacter salarius sp. nov., with the type strain R9SW1(T) ( =  LMG 27497(T)  =  JCM 19399(T)  =  CIP 110588(T)  =  KMM 7502(T)) and Marinobacter similis sp. nov., with the type strain A3d10(T) ( =  JCM 19398(T)  =  CIP 110589(T)  =  KMM 7501T), are proposed.